A method for preparing single-particle spherical artificial graphite

By forming single-particle spherical artificial graphite with a gradient composite structure through isostatic pressing densification, spheroidization treatment and resin crosslinking process, the density, kinetics and stability problems of existing spherical graphite in AIDC energy storage applications are solved, and the improvement of high energy density and long cycle life is achieved, which is suitable for AIDC energy storage and high-end energy storage fields.

CN123024480APending Publication Date: 2026-11-03FUJIAN KEDA NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611518553.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-29
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing spherical graphite anode materials suffer from problems such as low tap density, poor kinetic performance, high expansion rate, and poor stability due to simple modification processes in AIDC energy storage applications, which cannot meet the requirements of high energy density and long cycle life.

Method used

A gradient composite structure of single-particle spherical artificial graphite is formed by isostatic pressing densification, spheroidization, controlled oxidation modification and resin crosslinking processes. The process includes steps such as isostatic pressing densification, crushing and breaking, precision spheroidization, controlled oxidation, resin coating and dynamic stirring curing to construct a three-dimensional grid hard carbon skeleton.

Benefits of technology

It achieves improvements in high tap density, low expansion rate, long cycle life and high rate performance, adapts to the harsh operating conditions of AIDC energy storage, and reduces production costs and mass production defect rate, thereby improving product consistency and adaptability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123024480A_ABST
    Figure CN123024480A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of lithium ion battery negative electrode materials, and discloses a preparation method of single-particle spherical artificial graphite, S1: isostatic compaction; S2: scattering, breaking and fine shaping; S3: precise spheroidization treatment; S4: controllable oxidation modification; S5: resin fusion coating; S6: dynamic stirring solidification; S7: heat preservation stirring granulation shaping; S8: pre-carbonization; S9: ultrahigh-temperature graphitization; S10: cooling, screening and impurity removal; the isostatic compaction + spheroidization process + oxidation + resin crosslinking of the application form a three-dimensional grid hard carbon skeleton structure, long-term industry pain points of density rebound of the high-temperature heat treatment of the densified petroleum coke graphite are solved from the mechanism, and a technical blank of an existing process is made up; compared with a conventional single modification product, the application synchronously realizes the performance improvement of four major cores of high tap density, high rate, low expansion and long cycle, breaks through the technical bottleneck of single performance improvement of traditional graphite, and accurately matches AIDC energy storage special working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of negative electrode materials for AIDC computing power storage in lithium-ion batteries, specifically a method for preparing single-particle spherical artificial graphite. Background Technology

[0002] Lithium-ion batteries have become the mainstream power source for portable electronic devices, electric vehicles, and energy storage systems due to their advantages such as high energy density, long cycle life, and environmental friendliness. Among them, artificial graphite anode materials are currently the most mainstream anode materials for lithium-ion batteries because of their advantages such as high specific capacity, good electrochemical reversibility, low volume expansion rate, and wide availability of raw materials.

[0003] Currently, commercially available 8-9μm spherical petroleum coke-based artificial graphite in the industry is generally prepared using direct spheroidization, simple coating, and conventional carbonization processes. These processes lack densification modification and segmented shaping, resulting in multiple technical shortcomings and making them unsuitable for the demanding operating conditions of AIDC energy storage.

[0004] (1) Low tap density and limited energy storage capacity: conventional non-densified graphite particles have well-developed pores and loose powder packing. The difference in tap density under the same particle size directly leads to insufficient volumetric energy density of energy storage batteries, which cannot meet the large-capacity energy storage requirements of AIDC. Although the industry's conventional isostatic pressing densification process can improve the initial density, the densified particles are metastable structures. During high-temperature heat treatment, pore rebound and structural relaxation are very likely to occur, and the tap density will eventually decrease significantly, and the densification modification effect will be completely ineffective.

[0005] (2) Poor dynamic performance and high expansion rate: Traditional graphite particles have a simple structure and no gradient composite structure. The lithium-ion conduction rate is slow and the polarization is severe under high-rate charge and discharge. At the same time, the graphite layer expands and deforms greatly during charge and discharge, which easily leads to structural peeling and collapse, resulting in short cycle life.

[0006] (3) The modification process is simple and the stability is poor: the existing modification methods are only simple physical resin coating and single spheroidization shaping. The interface bonding force is weak and there is no rigid constraint skeleton. It cannot solve multiple pain points such as high density rebound, high ratio difference and high expansion rate at the same time. The product consistency and working condition adaptability are poor. Summary of the Invention

[0007] The purpose of this invention is to provide a method for preparing single-particle spherical artificial graphite to solve the problems mentioned in the background art.

[0008] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing single-particle spherical artificial graphite, comprising: S1: Isostatic pressing densification: Petroleum coke powder is loaded into a mold and subjected to cold isostatic pressing to obtain densified petroleum coke blocks. S2: Dispersion, crushing and fine shaping: The dense petroleum coke block is dispersed, crushed and finely shaped to remove sharp-angled and irregular particles, and shaped powder is obtained. S3: Precision spheroidization treatment: The shaped powder is subjected to spheroidization treatment to control the median particle size D50 of the particles to be 8-9 μm, thereby obtaining a spherical graphite precursor; S4: Controllable oxidation modification: The spherical graphite precursor is placed in an oxygen-containing atmosphere and oxidized at 500-600°C to generate active functional groups on the particle surface, and the thickness of the oxide layer is controlled to be 1-2 μm. S5: Resin fusion coating: Mix the oxidized graphite powder with methylphenol resin, add silane coupling agent, and stir to make the resin uniformly coat the particle surface. S6: Dynamic stirring and curing: Under stirring conditions, heat preservation and curing treatment is carried out at 120-150℃ to allow the resin to initially crosslink; S7: Heat preservation, stirring, granulation and shaping: Under a protective atmosphere, stirring and heat preservation treatment at 550-650℃ is carried out to complete the granulation and shaping; S8: Pre-carbonization: The shaped powder is heated to 1100-1300℃ under a protective atmosphere for pre-carbonization treatment; S9: Ultra-high temperature graphitization: The pre-carbonized powder is graphitized at 2800-3200℃; S10: Cooling and sieving to remove impurities, resulting in single-particle spherical artificial graphite with a gradient composite structure.

[0009] Preferably, in S1, the pressure of cold isostatic pressing is 150-250 MPa, the holding time is 5-20 min, the fixed carbon of the petroleum coke powder raw material is ≥98.5%, the ash content is ≤0.3%, and the initial D50 is 25 μm.

[0010] Preferably, in S3, the sphericity of the spherical graphite precursor particles is ≥0.90.

[0011] Preferably, in S4, the oxygen-containing atmosphere is an air atmosphere or an oxygen-rich atmosphere with an oxygen content of 25% to 30%, the oxidation treatment temperature is 500 to 600°C, and the holding time is 1 to 3 hours.

[0012] Preferably, in S5, the amount of methylphenolic resin added is 5% to 10% of the mass of graphite powder, and the amount of silane coupling agent added is 0.5% to 2% of the mass of methylphenolic resin.

[0013] Preferably, in step S6, the stirring speed is 60-100 rpm, and the heat preservation and curing time is 1-3 hours.

[0014] Preferably, in S7, the protective atmosphere is a nitrogen atmosphere, the stirring speed is 50-80 rpm, and the holding time is 0.5-2 h.

[0015] Preferably, in step S8, the heating rate of the pre-carbonization is 3-8℃ / min and the holding time is 2-5h; in step (9), the holding time of the graphitization treatment is 3-6h.

[0016] Preferably, the obtained single-particle spherical artificial graphite has a micro-gradient structure that, from the inside out, includes a core highly crystalline graphite layer, an intermediate graphite-hard carbon transition layer, and a surface dense hard carbon composite layer.

[0017] Preferably, the obtained single-particle spherical artificial graphite has a tap density of 1.35–1.45 g / cm³, a D50 of 8–9 μm, an electrode expansion rate of 7.0%–8.5% after 3000 1C cycles, a 5C discharge capacity retention rate of 85.0%–88.5%, and ≥10000 cycles of 1C cycles to achieve a capacity retention rate of 80%.

[0018] Compared with the prior art, the beneficial effects of the present invention are:

[0019] This invention utilizes isostatic pressing densification, spheroidization, oxidation, and resin crosslinking to form a three-dimensional grid hard carbon skeleton structure. This addresses the long-standing industry pain point of density rebound during high-temperature heat treatment of densified petroleum coke graphite, and fills a technological gap in existing processes.

[0020] Comprehensive performance upgrade: Compared with conventional single-modification products, this invention simultaneously achieves four core performance improvements: high tapping, high rate of change, low expansion, and long cycle life. It breaks through the technical bottleneck of single-performance improvement of traditional graphite and is precisely matched to the special working conditions of AIDC energy storage.

[0021] High process stability and low mass production cost: The entire process adopts mature industrial equipment such as vertical reactors, tunnel kilns, and graphitization furnaces, and the process parameters are precise and controllable, without the need for additional complex equipment; the segmented solidification and granulation process simplifies the later screening and purification process, reduces the defect rate in mass production, saves production costs, and is easy to promote on a large scale.

[0022] Innovative structural design and wide adaptability: The unique gradient composite single-particle structure combines the advantages of high-density conductivity in the core with the advantages of rapid lithium storage and buffer expansion on the surface. It is suitable for AIDC computing power energy storage and can also be extended to high-end energy storage and power lithium battery fields, making the product highly versatile.

[0023] Excellent product consistency: Dynamic stirring and shaping throughout the process, no agglomeration, no structural damage, and the uniformity of the finished powder is far superior to that of conventional modified products, resulting in a significant improvement in batch stability of batteries.

[0024] The parts of the device not covered herein are the same as or can be implemented using existing technologies. Attached Figure Description

[0025] Figure 1 The curves show the capacity retention rate after 3000 cycles at a 1C rate.

[0026] Figure 2 A bar chart comparing the discharge capacity retention rate at different discharge rates;

[0027] Figure 3 A bar chart comparing the electrode expansion rate after 3000 cycles;

[0028] Figure 4 This is a cross-sectional density comparison diagram of artificial graphite in Example 1;

[0029] Figure 5 This is a cross-sectional density comparison diagram of artificial graphite in Comparative Example 1.

[0030] Figure 6 Comparative diagram showing the cross-sectional density of artificial graphite in Example 2;

[0031] Figure 7 This is a comparison diagram of the cross-sectional density of artificial graphite in Comparative Example 3.

[0032] Figure 8 This is a Raman surface scan comparison image of artificial graphite in Example 1;

[0033] Figure 9 Raman surface scan comparison image of artificial graphite in Comparative Example 1;

[0034] Figure 10 Raman surface scan comparison image of artificial graphite in Comparative Example 2;

[0035] Figure 11 Raman surface scan comparison image of artificial graphite in Comparative Example 3;

[0036] Figure 12 This is a process flow diagram of a method for preparing single-particle spherical artificial graphite according to the present invention. Detailed Implementation

[0037] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0038] Example 1: The present invention provides a technical solution: a method for preparing single-particle spherical artificial graphite.

[0039] Raw material preparation: Core matrix: calcined petroleum coke powder (fixed carbon ≥ 98.5%, ash content ≤ 0.3%, initial D50 ≈ 25 μm); Coating material: methylphenolic resin (solid content 50%, residual carbon rate ≥ 40%); Interface additive: silane coupling agent KH550.

[0040] The preparation steps include: S1, isostatic pressing densification: calcined petroleum coke powder is loaded into a rubber mold, placed in a cold isostatic pressing device, and held at 200MPa pressure for 10min to obtain a densified petroleum coke block, in which the original pores inside are greatly compressed. S2, Dispersion, Crushing and Fine Shaping: The block material is fed into the air jet mill to disperse and crush it, and then the particle shape is shaped by the shaping machine to remove sharp-angled and irregular particles, thus obtaining the pre-shaped powder. S3, Precision spheroidization treatment: The shaped powder is fed into a horizontal spheroidizer, and the diameter is precisely controlled through multi-stage air force classification, finally obtaining a spherical graphite precursor with D50=8.5μm and particle sphericity ≥0.92. S4, Controllable oxidation modification: The spheroidized powder is placed in a rotary kiln and heated to 550℃ in an air atmosphere for 2 hours. The thickness of the surface oxide layer is controlled to 1.5μm, so that active functional groups such as hydroxyl and carboxyl groups are generated on the particle surface. S5, Resin Fusion Coating: Oxidized graphite powder is put into a vertical reactor, 7% of methylphenol resin by mass of powder is added, and 1% of silane coupling agent KH550 by mass of resin is added at the same time. Stir at room temperature for 30 minutes to make the resin uniformly coat the surface of the particles. S6, Dynamic stirring and curing: Turn on the reactor heating and raise the temperature to 135℃. Maintain the stirring speed at 80rpm throughout the process and keep it at the temperature for 2 hours to allow the resin to initially cross-link and avoid the adhesion and agglomeration between particles. S7, heat preservation, stirring, granulation and shaping: continue to heat up to 600℃, maintain stirring speed of 60rpm under nitrogen protection atmosphere, heat preservation for 1h to complete granulation and shaping, fix the composite morphology of particles, and prevent particles from melting and sticking together during subsequent high temperature treatment. S8, continuous pre-carbonization: The shaped powder is fed into a tunnel kiln and heated to 1200℃ at 5℃ / min under nitrogen protection. The pre-carbonization is completed by holding the temperature for 3 hours, so that the surface resin is completely carbonized to form a three-dimensional hard carbon constraint skeleton. S9, Ultra-high temperature graphitization: The pre-carbonized powder is loaded into a graphite crucible, placed in an intermediate frequency furnace, heated to 3000℃ and held for 4 hours to complete the deep graphitization of the matrix and the construction of the gradient composite structure. S10, after cooling, is screened through a 325-mesh vibrating screen to remove impurities, yielding the finished product: gradient composite structure single-particle spherical artificial graphite.

[0041]

[0042] Example 2: The present invention provides a technical solution: a method for preparing single-particle spherical artificial graphite.

[0043] Raw material preparation: Core matrix: calcined petroleum coke powder (fixed carbon ≥ 98.5%, ash content ≤ 0.3%, initial D50 ≈ 25 μm); Coating material: methylphenolic resin (solid content 50%, residual carbon rate ≥ 40%); Interface additive: titanate coupling agent.

[0044] The preparation steps include: S1, isostatic pressing densification: calcined petroleum coke powder is loaded into a rubber mold, placed in a cold isostatic pressing device, and held at 200MPa pressure for 10min to obtain a densified petroleum coke block, in which the original pores inside are greatly compressed. S2, Dispersion, Crushing and Fine Shaping: The block material is fed into the air jet mill to disperse and crush it, and then the particle shape is shaped by the shaping machine to remove sharp-angled and irregular particles, thus obtaining the pre-shaped powder. S3, Precision spheroidization treatment: The shaped powder is fed into a horizontal spheroidizer, and the diameter is precisely controlled through multi-stage air force classification, finally obtaining a spherical graphite precursor with D50=8.5μm and particle sphericity ≥0.92. S4, Controllable oxidation modification: The spheroidized powder is placed in a rotary kiln and heated to 550℃ in an air atmosphere for 2 hours. The thickness of the surface oxide layer is controlled to 1.5μm, so that active functional groups such as hydroxyl and carboxyl groups are generated on the particle surface. S5, Resin Fusion Coating: Oxidized graphite powder is put into a vertical reactor, 7% of the powder mass of methylphenol resin is added, and 1% of the resin mass of titanate coupling agent is added at the same time. Stir at room temperature for 30 minutes to make the resin uniformly coat the particle surface. S6, Dynamic stirring and curing: Turn on the reactor heating and raise the temperature to 135℃. Maintain the stirring speed at 80rpm throughout the process and keep it at the temperature for 2 hours to allow the resin to initially cross-link and avoid the adhesion and agglomeration between particles. S7, heat preservation, stirring, granulation and shaping: continue to heat up to 600℃, maintain stirring speed of 60rpm under nitrogen protection atmosphere, heat preservation for 1h to complete granulation and shaping, fix the composite morphology of particles, and prevent particles from melting and sticking together during subsequent high temperature treatment. S8, continuous pre-carbonization: The shaped powder is fed into a tunnel kiln and heated to 1200℃ at 5℃ / min under nitrogen protection. The pre-carbonization is completed by holding the temperature for 3 hours, so that the surface resin is completely carbonized to form a three-dimensional hard carbon constraint skeleton. S9, Ultra-high temperature graphitization: The pre-carbonized powder is loaded into a graphite crucible, placed in an intermediate frequency furnace, heated to 3000℃ and held for 4 hours to complete the deep graphitization of the matrix and the construction of the gradient composite structure. S10, after cooling, is screened through a 325-mesh vibrating screen to remove impurities, yielding the finished product: gradient composite structure single-particle spherical artificial graphite.

[0045] Example 3: The present invention provides a technical solution: a method for preparing single-particle spherical artificial graphite.

[0046] Raw material preparation: Core matrix: calcined petroleum coke powder (fixed carbon ≥ 98.5%, ash content ≤ 0.3%, initial D50 ≈ 25 μm); Coating raw material: methylphenolic resin (solid content 50%, residual carbon rate ≥ 40%); Interface additives: titanate coupling agent; phenolic modified resin, epoxy resin.

[0047] The preparation steps include: S1, isostatic pressing densification: calcined petroleum coke powder is loaded into a rubber mold, placed in a cold isostatic pressing device, and held at 200MPa pressure for 10min to obtain a densified petroleum coke block, in which the original pores inside are greatly compressed. S2, Dispersion, Crushing and Fine Shaping: The block material is fed into the air jet mill to disperse and crush it, and then the particle shape is shaped by the shaping machine to remove sharp-angled and irregular particles, thus obtaining the pre-shaped powder. S3, Precision spheroidization treatment: The shaped powder is fed into a horizontal spheroidizer, and the diameter is precisely controlled through multi-stage air force classification, finally obtaining a spherical graphite precursor with D50=8.5μm and particle sphericity ≥0.92. S4, Controllable oxidation modification: The spheroidized powder is placed in a rotary kiln and heated to 550℃ in an air atmosphere for 2 hours. The thickness of the surface oxide layer is controlled to 1.5μm, so that active functional groups such as hydroxyl and carboxyl groups are generated on the particle surface. S5, Resin Fusion Coating: Oxidized graphite powder is added to a vertical reactor, along with 7% methylphenolic resin by weight of the powder, 5-10% phenolic modified resin or epoxy resin by weight of the methylphenolic resin, and 1% titanate coupling agent by weight of the methylphenolic resin. The mixture is stirred at room temperature for 30 minutes to ensure that the resin uniformly coats the particle surface. By using a small amount of phenolic modified resin / epoxy resin to replace pure methylphenolic resin, the toughness of the surface hard carbon can be finely adjusted while retaining the cross-linking bone formation mechanism, further optimizing the product's expansion performance. S6, Dynamic stirring and curing: Turn on the reactor heating and raise the temperature to 135℃. Maintain the stirring speed at 80rpm throughout the process and keep it at the temperature for 2 hours to allow the resin to initially cross-link and avoid the adhesion and agglomeration between particles. S7, heat preservation, stirring, granulation and shaping: continue to heat up to 600℃, maintain stirring speed of 60rpm under nitrogen protection atmosphere, heat preservation for 1h to complete granulation and shaping, fix the composite morphology of particles, and prevent particles from melting and sticking together during subsequent high temperature treatment. S8, continuous pre-carbonization: The shaped powder is fed into a tunnel kiln and heated to 1200℃ at 5℃ / min under nitrogen protection. The pre-carbonization is completed by holding the temperature for 3 hours, so that the surface resin is completely carbonized to form a three-dimensional hard carbon constraint skeleton. S9, Ultra-high temperature graphitization: The pre-carbonized powder is loaded into a graphite crucible, placed in an intermediate frequency furnace, heated to 3000℃ and held for 4 hours to complete the deep graphitization of the matrix and the construction of the gradient composite structure. S10, after cooling, is screened through a 325-mesh vibrating screen to remove impurities, yielding the finished product: gradient composite structure single-particle spherical artificial graphite.

[0048] Please refer to Example 4 as well. Figures 1-12 In this embodiment, to further verify the technical effect of the process of the present invention, one optimal embodiment, namely embodiment one, is set up and compared with three control comparisons using a unified testing method.

[0049] Specific embodiments and comparative examples are provided for verification.

[0050] Example 1: The present invention uses isostatic pressing densification of artificial graphite, spheroidization process, oxidation, and resin crosslinking to form a three-dimensional grid hard carbon skeleton structure;

[0051] Comparative Example 1 (Conventional commercial process: no densification + no oxidative crosslinking + simple coating)

[0052] The isostatic pressing densification and controlled oxidation modification processes were omitted. Petroleum coke was directly spheroidized and coated with 3% methylphenol resin using a conventional impregnation method. After being cured at 120°C, it was directly pre-carbonized at 1200°C and graphitized at 3000°C. The remaining raw materials, parameters and test conditions were the same as in Example 1.

[0053] Comparative Example 2 (Isostatic pressing but no oxidative crosslinking + segmented shaping: simulating densification and springback)

[0054] The isostatic pressing densification process is retained, but the controlled oxidation modification and 600℃ heat treatment and stirring granulation and shaping processes are omitted. After resin coating, the resin is directly allowed to stand and cure, pre-carbonize, and graphitize. The remaining raw materials, parameters and test conditions are the same as in Example 1.

[0055] Comparative Example 3 (conventional spheroidization + single resin coating, no gradient structure)

[0056] Without isostatic pressing densification and controlled oxidation, 5% methylphenol resin is directly coated after spheroidization. There is no segmented stirring and shaping process. After static curing, it is carbonized and graphitized. The remaining raw materials, parameters and test conditions are the same as in Example 1.

[0057] The artificial graphite prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were subjected to performance tests according to standardized testing methods.

[0058] Standardized testing methods

[0059] (1) Particle size and particle size distribution were tested using a laser particle size analyzer (Malvin MasterSizer3000), with anhydrous ethanol as the dispersion medium. The median particle size D50 of the sample was tested after ultrasonic dispersion for 30s.

[0060] (2) The tapped density test was performed using a powder tapped density meter. 10.00g of graphite powder was weighed and poured into a 10mL graduated cylinder. The number of tapping times was set to 3000 and the tapping frequency was set to 250 times / minute. After the tapping was completed, the volume of the powder was read and the tapped density was calculated as "powder mass / tapped volume".

[0061] (3) Electrochemical performance testing Electrode preparation: Artificial graphite negative electrode material, acetylene black conductive agent, CMC thickener and SBR binder are mixed in a mass ratio of 95:1.5:1:2.5, deionized water is added and stirred to form a uniform slurry, which is then coated on an 8μm copper foil current collector, vacuum dried at 110℃ for 12h, and then rolled to a surface density of 10mg / cm², and cut into negative electrode sheets with a diameter of 14mm. Battery assembly: The full cell uses NCM622 ternary cathode with a positive-to-negative capacity ratio of 1:1.1. Celgard2400 is used as the separator, and the electrolyte is 1 mol / L LiPF6 / EC:DMC = 1:1 (volume ratio) + 5% FEC. The assembly is carried out in an argon atmosphere glove box. Charge and discharge test: On the Blue Battery test system, under a constant temperature environment of 25℃ and a voltage range of 2.75~4.25V, activation was first completed by charging and discharging at a constant current of 0.1C for 3 cycles, and then the rate and cycle life tests were performed.

[0062] (4) Interfacial impedance and lithium-ion diffusion coefficient were tested using an electrochemical workstation with an alternating current impedance (EIS) test at a frequency range of 10 Hz. -2 ~10 5 Hz, AC amplitude 5mV; the lithium-ion diffusion coefficient was calculated by potentiostatic intermittent titration (PITT).

[0063] (5) The electrode expansion rate test is performed by using a spiral micrometer to test the center thickness of the electrode before and after the cycle. Five points are tested for each electrode and the average value is taken. The electrode expansion rate is calculated according to the formula: Electrode expansion rate = (Electrode thickness after cycle - Initial electrode thickness) / Initial electrode thickness × 100%.

[0064] Overall product performance indicators:

[0065] The performance of the product of this invention compared with that of conventional 8-9μm artificial graphite in the industry is as follows: Test performance items Product data of this invention Comparative data Improvement / Enhancement of Effect Single particle D50 size (μm) 8~9 8~9 / Tap density (g / cm³) 1.35~1.45 1.10~1.20 Tap density increased by 12%–23%. First-time Coulomb efficiency (%) 92.2~93.0 91.5~92.5 Achieving high-quality standards for power battery applications, the SEI film forms more uniformly and stably with no additional lithium loss, balancing high tap density and first-time efficiency. 0.1C reversible specific capacity (mAh / g) 348~352 345~350 The matrix lithium storage capacity is stable and meets the target; the high-tapping modification process has no additional capacity loss, meeting the design requirements of high-energy-density batteries. Initial 0.5C discharge capacity retention (%, relative to 0.1C capacity) 98.0~99.0 95.0~96.5 At low rates, the capacity is fully utilized and the polarization is smaller. Initial 1C discharge capacity retention (%, relative to 0.1C capacity) 96.5~97.5 92.0~94.0 Less capacity loss and higher energy efficiency at normal charge / discharge rates Initial 2C discharge capacity retention (%, relative to 0.1C capacity) 93.0~95.0 82.0~85.0 Its performance advantage is significant at medium to high magnification, with polarization increase far lower than that of comparative products. Initial 3C discharge capacity retention (%, relative to 0.1C capacity) 90.0~92.0 70.0~73.0 The high-rate charging and discharging capability has been greatly improved, making it suitable for high-current operating conditions. Initial 5C discharge capacity retention (%, relative to 0.1C capacity) 85.0~88.5 55.0~59.0 High-rate capacity retention is improved by more than 60%, and fast charging and large discharge capabilities are comprehensively leading. Interfacial charge transfer impedance Rct (mΩ) 15~19 30~38 Reduced by more than 50%, with significantly optimized interface dynamics, effectively improving fast charging performance and rate response. <![CDATA[Lithium ion diffusion coefficient D (×10⁻¹ 0 cm² / s)]]> 2.5~3.0 1.3~1.7 Improved by over 80%, with a shorter lithium-ion transmission path and significantly faster charging speed, making it suitable for high-rate fast charging conditions. Capacity retention rate (%) after 3000 1C cycles 90.0~93.5 75~78 Improved by more than 18%, with long-cycle stability far exceeding that of conventional modified products in the industry. Number of cycles from 1C to 80% capacity retention ≥10000 4500~5000 The performance has been improved by more than 100%, fully meeting the long-cycle evaluation standards for power batteries and AIDC energy storage scenarios. Capacity retention at 5C rate after 3000 cycles (relative to initial 1C capacity) (%) 85.0~88.5 55~59 Improved by more than 60%, with no significant degradation in fast charging performance after long-term cycling. Electrode expansion rate (%) after 10 1C cycles 7.0~8.5 15~17 Reduced by more than 45%, exhibiting outstanding low expansion characteristics, effectively suppressing electrode deformation and cracking during cycling.

[0066] Note: All electrochemical performance tests were conducted under full-cell conditions, as follows: ① Cathode material: NCM622 ternary cathode; ② Electrolyte system: 1 mol / L LiPF6 / EC:DMC = 1:1 (volume ratio), with 5% FEC additive; ③ Test environment: constant 25℃; ④ Voltage range: 2.75V~4.25V; ⑤ Activation process: 3 cycles of 0.1C constant current charge-discharge to ensure sufficient electrolyte wetting and stable SEI interface formation; ⑥ Cycle performance test: 1C constant current charge-discharge regime was used to statistically analyze capacity decay and electrode expansion rate; ⑦ Rate performance test: starting at an initial 1C... Based on discharge capacity, the capacity retention rate at different rates is statistically analyzed; ⑧ 80% capacity retention rate cycle count: This is a common lifespan assessment indicator for power batteries, used to define the effective service life of the battery; ⑨ Long cycle life description: The indicator of "1C cycle to 80% capacity retention rate ≥ 10,000 times" in this scheme is calculated by extrapolation from the measured capacity decay rate of 3,000 complete cycles through the lifespan decay model commonly used in the lithium battery industry; If full-process continuous actual testing is adopted, the complete test cycle of 10,000 1C charge-discharge cycles is approximately 2.4 to 2.6 years (including standard test procedures such as constant voltage charging and static placement).

[0067] Performance test results of the examples and comparative examples

[0068] Note: 1. All data in the table were obtained using the same test methods and conditions as described above;

[0069] The table below shows the statistical analysis results of Raman spectral surface scanning, used to characterize the structural order, homogeneity, and graphitization degree of graphite materials.

[0070]

[0071] Results Analysis

[0072] AD / AG represents the ratio of disordered carbon peak area to graphite carbon peak area. It is the ratio of structural disorder. The higher the value, the higher the content of disordered carbon (hard carbon / defects) in the material.

[0073] STD stands for Standard Deviation, which is the standard deviation of the AD / AG ratio. It reflects the structural uniformity within the scanned area; the lower the value, the more uniform the structure.

[0074] COV stands for Coefficient of Variation. It is the ratio of the standard deviation to the mean. It reflects the dispersion of the data; the lower the value, the smaller the AD / AG fluctuation at each point in the area scanned, and the more uniform the structure.

[0075] The highest AD / AG ratio (1.607) demonstrates that the particle surface in Example 1 forms a rich three-dimensional hard carbon skeleton (resin oxidative crosslinking carbonization product), which is the structural basis for suppressing high-temperature density rebound and providing a fast lithium-ion transport channel.

[0076] The lowest STD and COV values ​​demonstrate that the hard carbon in Example 1 is uniformly covered on the surface of the particles, rather than locally aggregated, verifying the effectiveness of the "controlled oxidation → resin crosslinking → segmented stirring and shaping" process in ensuring structural uniformity.

[0077] Although Comparative Example 2 (non-oxidative crosslinking + segmented shaping) underwent isostatic pressing densification, its COV was as high as 0.540, indicating that the densification lacked the constraint of a hard carbon skeleton. During the high-temperature graphitization process, the structure was relaxed and the graphitization was uneven, resulting in a significant decrease in the measured tap density (1.22 g / cm³).

[0078] Although Comparative Example 2 underwent isostatic compaction, the lack of oxidative crosslinking and hard carbon skeleton constraint led to pore rebound after high-temperature graphitization, resulting in a significant decrease in tap density. This demonstrates that the coupling process of "isostatic compaction compaction + three-dimensional hard carbon skeleton anti-rebound" in this invention is the core to achieving high tap performance. Meanwhile, Example 1 significantly outperformed all comparative examples in terms of rate performance, cycle life, and electrode expansion rate, verifying the comprehensive performance advantages of the gradient composite single-particle structure, which can fully adapt to the harsh working conditions of AIDC computing power storage.

[0079] This invention utilizes isostatic pressing densification, spheroidization, oxidation, and resin crosslinking to form a three-dimensional grid hard carbon skeleton structure. This addresses the long-standing industry pain point of density rebound during high-temperature heat treatment of densified petroleum coke graphite, and fills a technological gap in existing processes.

[0080] Comprehensive performance upgrade: Compared with conventional single-modification products, this invention simultaneously achieves four core performance improvements: high tapping, high rate of change, low expansion, and long cycle life. It breaks through the technical bottleneck of single-performance improvement of traditional graphite and is precisely matched to the special working conditions of AIDC energy storage.

[0081] High process stability and low mass production cost: The entire process adopts mature industrial equipment such as vertical reactors, tunnel kilns, and graphitization furnaces, and the process parameters are precise and controllable, without the need for additional complex equipment; the segmented solidification and granulation process simplifies the later screening and purification process, reduces the defect rate in mass production, saves production costs, and is easy to promote on a large scale.

[0082] Innovative structural design and wide adaptability: The unique gradient composite single-particle structure combines the advantages of high-density conductivity in the core with the advantages of rapid lithium storage and buffer expansion on the surface. It is suitable for AIDC computing power energy storage and can also be extended to high-end energy storage and power lithium battery fields, making the product highly versatile.

[0083] Excellent product consistency: Dynamic stirring and shaping throughout the process, no agglomeration, no structural damage, and the uniformity of the finished powder is far superior to that of conventional modified products, resulting in a significant improvement in batch stability of batteries.

[0084] Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

Claims

1. A method for preparing single-particle spherical artificial graphite, characterized in that: include: S1: Isostatic pressing densification: Petroleum coke powder is loaded into a mold and subjected to cold isostatic pressing to obtain densified petroleum coke blocks. S2: Dispersion, crushing and fine shaping: The dense petroleum coke block is dispersed, crushed and finely shaped to remove sharp-angled and irregular particles, and shaped powder is obtained. S3: Precision spheroidization treatment: The shaped powder is subjected to spheroidization treatment to control the median particle size D50 of the particles to be 8-9 μm, thereby obtaining a spherical graphite precursor; S4: Controllable oxidation modification: The spherical graphite precursor is placed in an oxygen-containing atmosphere and oxidized at 500-600°C to generate active functional groups on the particle surface, and the thickness of the oxide layer is controlled to be 1-2 μm. S5: Resin fusion coating: Mix the oxidized graphite powder with methylphenol resin, add silane coupling agent or titanate coupling agent, and stir to make the resin uniformly coat the particle surface. S6: Dynamic stirring and curing: Under stirring conditions, heat preservation and curing treatment is carried out at 120-150℃ to allow the resin to initially crosslink; S7: Heat preservation, stirring, granulation and shaping: Under a protective atmosphere, stirring and heat preservation treatment at 550-650℃ is carried out to complete the granulation and shaping; S8: Pre-carbonization: The shaped powder is heated to 1100-1300℃ under a protective atmosphere for pre-carbonization treatment; S9: Ultra-high temperature graphitization: The pre-carbonized powder is graphitized at 2800-3200℃; S10: Cooling and sieving to remove impurities, resulting in single-particle spherical artificial graphite with a gradient composite structure.

2. The method for preparing single-particle spherical artificial graphite according to claim 1, characterized in that: In S1, the pressure of cold isostatic pressing is 150-250 MPa, the holding time is 5-20 min, the fixed carbon of the petroleum coke powder raw material is ≥98.5%, the ash content is ≤0.3%, and the initial D50 is 25 μm.

3. The method for preparing single-particle spherical artificial graphite according to claim 1, characterized in that: In S3, the sphericity of the spherical graphite precursor particles is ≥0.

90.

4. The method for preparing single-particle spherical artificial graphite according to claim 1, characterized in that: In S4, the oxygen-containing atmosphere is an air atmosphere or an oxygen-rich atmosphere with an oxygen content of 25% to 30%, the oxidation treatment temperature is 500 to 600°C, and the holding time is 1 to 3 hours.

5. The method for preparing single-particle spherical artificial graphite according to claim 1, characterized in that: In S5, the amount of methylphenolic resin added is 5% to 10% of the mass of graphite powder, and the amount of silane coupling agent or titanate coupling agent added is 0.5% to 2% of the mass of methylphenolic resin.

6. The method for preparing single-particle spherical artificial graphite according to claim 1, characterized in that: In S6, the stirring speed is 60-100 rpm, and the heat preservation and curing time is 1-3 hours.

7. The method for preparing single-particle spherical artificial graphite according to claim 1, characterized in that: In S7, the protective atmosphere is nitrogen, the stirring speed is 50-80 rpm, and the holding time is 0.5-2 h.

8. The method for preparing single-particle spherical artificial graphite according to claim 1, characterized in that: In step S8, the heating rate of the pre-carbonization is 3-8℃ / min and the holding time is 2-5h; in step (9), the holding time of the graphitization treatment is 3-6h.

9. The method for preparing single-particle spherical artificial graphite according to claim 1, characterized in that: The obtained single-particle spherical artificial graphite has a micro-gradient structure that, from the inside out, consists of a core highly crystalline graphite layer, an intermediate graphite-hard carbon transition layer, and a surface dense hard carbon composite layer.

10. The method for preparing single-particle spherical artificial graphite according to claim 9, characterized in that: The obtained single-particle spherical artificial graphite has a tap density of 1.35–1.45 g / cm³, a D50 of 8–9 μm, an electrode expansion rate of 7.0%–8.5% after 3000 1C cycles, a 5C discharge capacity retention rate of 85.0%–88.5%, and ≥10000 cycles to achieve a 80% capacity retention rate at 1C.